Surabaya Paradiplomacy: A Strategy for Regional Autonomy within the Framework of StateSovereignty - Muhammad Fajhriyadi Hastira; Galank Pratama; Muh. Zuhud Al Khaer Zahir (JGov: Journal of Governmentality, 2025)
Paradiplomacy is an important strategy in the context of regional autonomy that allows local governments to build international cooperation to support local development. This article discusses how paradiplomacy becomes a means of reactualizing the authority of local governments within the framework of national policies, and how these activities have an impact on the effectiveness of local development while maintaining state sovereignty. This study uses a qualitative approach with a literature study method, and highlights the practices of Surabaya City Government as a case study. Data was obtained from official documents, academic publications, international cooperation reports, and government regulations. The results of the study show that Surabaya actively cooperates abroad through sister city schemes with various world cities, producing benefits in the fields of education, environment, creative economy, and strengthening human resource capacity. However, the effectiveness of paradiplomacy is highly dependent on synergy with the central government and compliance with national regulations governing foreign affairs, as the exclusive authority of the state. The findings confirm that paradiplomacy can be a strategic local development instrument if it is managed purposefully and in strong coordination with national policies, so that it does not interfere with the principles of state sovereignty and integrity.